Spy&Go purification of SpyTag-proteins using pseudo-SpyCatcher to access an oligomerization toolbox - Irsyad N. A. Khairil Anuar (Nature Portfolio, 2019)
Peptide tags are important for protein purification but have minimal benefits afterwards. Here the authors present Spy&Go, which uses rational engineering of the SpyDock protein to capture SpyTag peptides without requiring an irreverisble isopeptide bond.